China's Particle Therapy Equipment Market: Opportunities Outweigh Challenges - Dai, Zhongying; Ma, Yuanyuan; Li, Qiang (Frontiers in Public Health, 2020)
Since 2019, china has been the second largest medical device market in the world. However, China's MedTech industry especially the particle therapy equipment field still faces the influence of policy, fluctuation of market demanding, strengthening of industry supervision and even geopolitical realities. This paper reviews the market prospect of particle therapy medical devices from the perspective of China's medical device policy and demand information analysis, which is conducive to the research on the industrial layout of particle therapy medical physics, and also helps high-performance medical device manufacturers to expand their business visions. MedTech manufacturers should actively adjust their business strategy, implement scientific and technological innovation on the basis of compliance with industry regulatory requirements in order to seize opportunities from challenges and gain profits growth.